2023
DOI: 10.1002/adfm.202214245
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Flexible Materials from Nanocellulose

Abstract: With the increase of environmental pollution and depletion of fossil fuel resources, the utilization of renewable biomass resources for developing functional materials or fine chemicals is of great value and has attracted considerable attention. Nanocellulose, as a well-known renewable nanomaterial, is regarded as a promising nano building block for advanced functional materials owing to its unique structure and properties, as well as natural abundance. Typically, its high mechanical strength, structural flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 232 publications
(453 reference statements)
0
23
0
Order By: Relevance
“…With highly ordered aggregation structure, flexible crystals might be engineered to exhibit fascinating optical, electrical, and mechanical properties, promising their potential flexible electronics and actuation applications. On account of the broad applications prospect in the fields of information sensing, biomedicine, ,, wearable devices, laser media, , fluorescence detection, renewable biomass resources development, etc., flexible crystals have attracted increasing attention from academia and industry.…”
Section: Application Prospects Of Flexible Crystalsmentioning
confidence: 99%
“…With highly ordered aggregation structure, flexible crystals might be engineered to exhibit fascinating optical, electrical, and mechanical properties, promising their potential flexible electronics and actuation applications. On account of the broad applications prospect in the fields of information sensing, biomedicine, ,, wearable devices, laser media, , fluorescence detection, renewable biomass resources development, etc., flexible crystals have attracted increasing attention from academia and industry.…”
Section: Application Prospects Of Flexible Crystalsmentioning
confidence: 99%
“…The stable structure and robust mechanical properties of nanocellulose hydrogels can ensure the reliability of sensors in various environments and reduce the loss in their performance caused by mechanical stress. 185,186 Moreover, the excellent dispersion property of nanocellulose facilitates the dispersion of conductive materials in the hydrogels, thereby further improving the sensitivity and response speed of the sensors. 187 Consequently, rationally designed nanocellulose hydrogels satisfy the sensor response sensitivity and precision criteria, providing a new option for the development of sensors.…”
Section: Applicationsmentioning
confidence: 99%
“…Cellulose is one of the most abundant and renewable natural polymers in nature with superior biocompatibility, tunable surface chemistry, and excellent mechanical properties. , Different types of functionalized cellulose, such as regenerated cellulose, cellulose nanofibers (CNF), and hydroxyethyl cellulose, can be prepared accordingly. , Methylcellulose (MC) is a cellulose derivative obtained by grafting a methyl group onto a hydroxyl group of cellulose through etherification. Compared to other derivatives, MC has the advantages of low cost, good water solubility, excellent flexibility and curvature, and rapid biodegradation, which has been widely used in electronics such as electrochemical actuation and energy storage. For example, Lim et al reported a multifunctional composite quasi-solid polymer electrolyte based on methylcellulose and LiCIO 4 salts, and the fabricated capacitors exhibited high specific capacitance and excellent cyclability .…”
Section: Introductionmentioning
confidence: 99%